Six-year follow up of atraumatic restorative treatment restorations placed in Chinese school children - Lo ECM, Holmgren CJ, Hu D, van Palenstein Helderman W. (Blackwell Synergy, 2007)
This study aimed to evaluate the clinical performance of atraumatic restorative treatment (ART) restorations placed in school children in China over a 6-year period.